When Words Fail: Exploring Speaking Anxiety Among ESL Learners - Tampubolon, Muhammad Ahsan (IJLHE: International Journal of Language, Humanities, and Education, 2025)
This study examined the speaking anxiety levels and sources among 130 English as a Second Language (ESL) students at Universitas Pamulang, across basic and intermediate courses. Speaking competence is crucial in today's globalized world, yet anxiety often hinders learners' confidence and participation. Using a quantitative survey, the adapted "Sources of Speaking Anxiety for Learners of English as a Second Language Scale" by Young (1990) was administered. Descriptive statistics, t-tests, and ANOVA were used to analyze the data, looking at anxiety levels and their connection to gender and proficiency. Results showed that over half of the students (53.49%) experienced some speaking anxiety. Interestingly, no significant differences were found based on gender or overall proficiency, except for one specific item: intermediate learners showed higher anxiety when interacting with peers of the opposite sex. The primary sources of anxiety identified were fear of making mistakes, unfamiliarity with topics, fear of evaluation, and limited vocabulary. Conversely, speaking with classmates and engaging in role-play activities were less anxiety-provoking. These findings highlight the need for educators to address both the psychological and teaching aspects of language instruction. The study recommends implementing learner-centered approaches, interactive speaking tasks, and supportive classroom environments to alleviate performance pressure. The results have implications for developing more inclusive and effective ESL instruction, especially where students have limited English exposure outside the classroom. Future research could benefit from qualitative data and larger, more diverse samples.